P136 Relationship between progression of lung disease in alpha-1 antitrypsin deficiency and cardiovascular risk. (15th November 2016) - Hall, C; Samanta, S; Verma, N; Gooptu, B; Hurst, JR
Abstract : Introduction: Patients with alpha-1 antitrypsin deficiency (AATD) who are homozygous for the mutated Z allele (PiZZ) typically present with emphysema and liver cirrhosis, caused by the uncontrolled action of neutrophil elastase in the lungs and toxic gain-of-function AAT polymer aggregates in the ER of hepatocytes. The link between cardiovascular disease and COPD is widely accepted, but is less well understood in AATD. This study aimed to investigate how markers of lung function severity and the rate of disease progression are associated with cardiovascular risk in a cohort of PiZ patients. Methods: Cardiovascular (CV) risk was determined by the degree of arterial stiffness, measured using aortic pulse wave velocity (aPWV). This was recorded with the Vicorder device which uses the transcutaneous distance between the common carotid and femoral arteries, and the time delay between the feet of the 2 diastolic pulse waveforms to calculate the pulse velocity. Cardiovascular risk was additionally assessed using the QRISK2 algorithm. Pulmonary function was evaluated using FEV1, KCO and RV%TLC, and the degree of AATD disease progression used previous pulmonary function test (PFT) data to determine the rate of lung function decline. Results: We enrolled 48 PiZZ AATD patients (mean (SD) age 52.9 (15.9) years, 19 male) and found significant relationships (denoted by: **p < 0.01 and *p < 0.05) between both aPWV and QRISK2 and the degree of airflow obstruction (FEV1: r = −0.470**, rho = −0.325*), emphysema (KCO: r = −0.493**, r = −0.411**) and hyperinflation (RV%TLC: r = 0.550**, r = 0.433**). Including only patients with ≥3 PFT results, we found a significant relationship between emphysema progression and calculated but not measured cardiovascular risk: KCO change vs. QRISK2 (r = −0.549, p = 0.015, n = 19). Conclusions: Reduced lung function was associated with a greater magnitude of measured and calculated cardiac risk in the AATD cohort. However AATD-mediated lung disease progression was not significantly related to measured CV risk – an exception being a significant relationship between the rate of decline of KCO and QRISK2.